Subchronic exposure to concentrated ambient PM2.5 perturbs gut and lung microbiota as well as metabolic profiles in mice. (1st March 2021) - Ran, Zihan; An, Yanpeng; Zhou, Ji; Yang, Jingmin; Zhang, Youyi; Yang, Jingcheng; Wang, Lei; Li, Xin; Lu, Daru; Zhong, Jiang; Song, Huaidong; Qin, Xingjun; et al.
Abstract: Exposure to ambient fine particular matter (PM2.5) are linked to an increased risk of metabolic disorders, leading to enhanced rate of many diseases, such as inflammatory bowel disease (IBD), cardiovascular diseases, and pulmonary diseases; nevertheless, the underlying mechanisms remain poorly understood. In this study, BALB/c mice were exposed to filtered air (FA) or concentrated ambient PM2.5 (CPM) for 2 months using a versatile aerosol concentration enrichment system(VACES). We found subchronic CPM exposure caused significant lung and intestinal damage, as well as systemic inflammatory reactions. In addition, serum and BALFs (bronchoalveolar lavage fluids) metabolites involved in many metabolic pathways in the CPM exposed mice were markedly disrupted upon PM2.5 exposure. Five metabolites (glutamate, glutamine, formate, pyruvate and lactate) with excellent discriminatory power (AUC = 1, p < 0.001) were identified to predict PM2.5 exposure related toxicities. Furthermore, subchronic exposure to CPM not only significantly decreased the richness and composition of the gut microbiota, but also the lung microbiota. Strong associations were found between several gut and lung bacterial flora changes and systemic metabolic abnormalities. Our study showed exposure to ambient PM2.5 not only caused dysbiosis in the gut and lung, but also significant systemic and local metabolic alterations. Alterations in gut and lung microbiota were strongly correlated with metabolic abnormalities. Our study suggests potential roles of gut and lung microbiota in PM2.5 caused metabolic disorders. Graphical abstract: Image 1 Highlights: PM2.5 exposure caused lung/intestinal damage and systemic inflammatory reactions. PM2.5 led to marked metabolic changes in the serum and bronchoalveolar lavage fluids. Glutamate, glutamine, formate, pyruvate and lactate were PM2.5 toxicity markers. PM2.5 drastically decreased the richness and composition of gut and lung microbiota. Gut/lung microbiota alterations strongly correlated with metabolic abnormalities. Abstract : Gut and lung microbiota alterations caused by subchronic exposure to CPM were strongly correlated with metabolic abnormalities.